ANALISIS KEMAMPUAN LITERASI DIGITAL MELALUI PENUGASAN POSTER MENU MAKANAN MENGGUNAKAN APLIKASI CANVA PADA PESERTA DIDIK SEKOLAH DASAR - Stiawan, Dani; Purnamasari, Veryliana; Suwarti, Suwarti; Damayani, Aries Tika (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
Digital literacy itself is a person's ability to manage, access, communicate and utilize electronic devices in an effort to obtain information. This research aims to analyze the digital literacy skills of grade 6 students at SDN Bugangan 01 through the assignment of making food menu posters using the Canva application. This research was conducted in July 2024. The method used by researchers is a descriptive qualitative method by describing the analysis that has been carried out. The data source involved grade 6 teachers and grade 6 students at SDN Bugangan 01, totaling 26 students. The data collection techniques used in this research were observation, interviews and documentation. Based on the observations that have been made, it can be concluded that the digital literacy skills of class 6 students at SDN Bugangan 01 through the assignment of food menu posters via the Canva application are good. Students can manage the Canva application well starting from entering the Canva application, being able to utilize the features on the Canva menu such as templates, fonts and other features in designing posters, downloading poster files to exiting the Canva application. Students also showed good results in the food menu poster assignment with an attractive design in accordance with students' creativity.